2017
DOI: 10.1177/0333102417737765
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled, parallel-group, multi-center study of the safety and efficacy of ADAM zolmitriptan for the acute treatment of migraine

Abstract: ObjectiveTo determine the efficacy, tolerability, and safety of ascending doses of Adhesive Dermally-Applied Microarray (ADAM) zolmitriptan versus placebo for acute migraine treatment.BackgroundADAM is a novel patient-administered system for intracutaneous drug administration. In a phase 1 pharmacokinetic study, zolmitriptan administered using ADAM had much faster absorption than oral administration with higher exposure in the first two hours.MethodsThis was a multicenter, randomized, double-blind, placebo-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 12 publications
7
50
1
1
Order By: Relevance
“…Initial models included all covariates, but the following variables were eliminated from the final model estimates because they did not significantly contribute to predicting the presence of the selected MBS: MIDAS, MHD frequency, medication overuse, MSSS, PROMIS Pain Interference, TPI, PHQ-2 anxiety, and PHQ-2 depression. b Monthly headache days over the past 90 days, divided by 3. c Responses to 12 ASC questions scored as 0 (never or rarely), 1 (less than half the time), and 2 (half the time or more), and summed (range 0-24), categories: none (0-2), mild (3)(4)(5), moderate (6)(7)(8), and severe (9 or more). The nausea MBS model found that men were less likely than women to designate nausea as their MBS (OR .77, 95% CI .66, .89).…”
Section: Resultsmentioning
confidence: 99%
“…Initial models included all covariates, but the following variables were eliminated from the final model estimates because they did not significantly contribute to predicting the presence of the selected MBS: MIDAS, MHD frequency, medication overuse, MSSS, PROMIS Pain Interference, TPI, PHQ-2 anxiety, and PHQ-2 depression. b Monthly headache days over the past 90 days, divided by 3. c Responses to 12 ASC questions scored as 0 (never or rarely), 1 (less than half the time), and 2 (half the time or more), and summed (range 0-24), categories: none (0-2), mild (3)(4)(5), moderate (6)(7)(8), and severe (9 or more). The nausea MBS model found that men were less likely than women to designate nausea as their MBS (OR .77, 95% CI .66, .89).…”
Section: Resultsmentioning
confidence: 99%
“…In this multicenter, randomized, double‐blind, placebo‐controlled, parallel group Phase 2b/3 study, patients treated with ADAM zolmitriptan 3.8 mg were significantly more likely to be pain‐free and/or MBS‐free at 2 hours post‐treatment than those receiving placebo 5. Approximately 80 patients per treatment group were sufficient to show a clear difference between an effective therapy and placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Pain freedom is now recommended in place of pain relief as a primary efficacy endpoint, as it is considered more clinically meaningful. It is also the recommended primary endpoint for acute migraine treatment trials by the International Headache Society 5. The major associated symptoms of migraine—photophobia, phonophobia, and nausea—are important for assessing a therapy's effect on the migraine, but all symptoms are not always present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations